Conyza Dicorides: Anew and Efficient Eco-Friendly Corrosion Inhibitor for Mild Steel in 1M HCl Solution - Khaled, Narjes I.; Sultan, Abd-Alwahab A.; Ibrahem, Hussein H.; Khalaf, Moayad N. (Sulaimani Journal for Pure and Applied Sciences, 2014)
The inhibitory effects of the ethanol extract of Conyza dioscoridis (EECD) on the corrosion of mild steel in a 1 M HCl solution were investigated by weight loss measurements at the temperature range of 25 °C to 65 °C. Results showed that the inhibition efficiency increased with increasing EECD concentration and decreased with increasing temperature. The inhibition efficiency of 2 g/L EECD reached approximately 94.87% at 25 °C. The thermodynamic functions of dissolution, activation energy, and adsorption processes were calculated and discussed. The adsorption of the additive followed the Langmuir adsorption isotherm.
Keywords: Mild steel Acid solution Weight loss Acid inhibition Adsorption processCorrosion inhibition